The Dutch Apollo 11 Goodwill display contains genuine Moon rocks - Thomas André Claude Zillhardt; Wim van Westrenen; Marianne Nuij; Ryan Warr; Zixian Su; Timothy Burnett (Communications Earth & Environment)
Abstract In the 1970s, US President Richard Nixon offered moon samples returned by the Apollo 11 and Apollo 17 missions to the leaders of the nations of the World. In this study, we used a combination of advanced X-ray analysis methods, including microtomography, tomosynthesis and hyperspectral chemical mapping to carry out a non-destructive forensic investigation of the Dutch Apollo 11 Goodwill sample, normally on display at the Boerhaave museum in the Netherlands. These powerful methods were uniquely able to non-destructively interrogate the samples encased in plastic without contact, providing 3D images of sample textures and compositional analysis, to assess whether the results agree with archive data on Apollo 11 coarse-grained soil sample number 10085, and to provide new insights on their origins. Our forensic investigation asked the question: were the rocks in the Dutch display actually picked up on the surface of the moon by Neil Armstrong and Buzz Aldrin?